2021
DOI: 10.3389/fendo.2020.621944
|View full text |Cite
|
Sign up to set email alerts
|

Quinolinate Phosphoribosyltransferase Promotes Invasiveness of Breast Cancer Through Myosin Light Chain Phosphorylation

Abstract: Perturbed Nicotinamide adenine dinucleotide (NAD+) homeostasis is involved in cancer progression and metastasis. Quinolinate phosphoribosyltransferase (QPRT) is the rate-limiting enzyme in the kynurenine pathway participating in NAD+ generation. In this study, we demonstrated that QPRT expression was upregulated in invasive breast cancer and spontaneous mammary tumors from MMTV-PyVT transgenic mice. Knockdown of QPRT expression inhibited breast cancer cell migration and invasion. Consistently, ectopic expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 48 publications
0
27
0
Order By: Relevance
“…When studying the function of people's tumors, most research on tumor-infiltrating immune cells (TIIC) pays attention to T cells. Others describe their reaction to rates of survival and immune checkpoint suppression [ 11 , 22 , 23 ]. This study provides a new reference to the developing research that discerns T cells as a positive prognostic factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When studying the function of people's tumors, most research on tumor-infiltrating immune cells (TIIC) pays attention to T cells. Others describe their reaction to rates of survival and immune checkpoint suppression [ 11 , 22 , 23 ]. This study provides a new reference to the developing research that discerns T cells as a positive prognostic factor.…”
Section: Discussionmentioning
confidence: 99%
“…The annotations of Gene Ontology (GO) associated with this type contain protein homodimerization activity and transfers activity, transferring pentyl groups [ 6 , 7 ]. Previous studies have reported that QPRT enhanced breast cancer invasiveness probably through purinergic signaling and might be a potential prognostic indicator and therapeutic target in breast cancer [ 8 11 ]. Our study found that QPRT has a clear correlation with the prognosis of BRCA.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al used in vivo and in vitro experiments to confirm that QPRT promotes growth, migration, and invasion of breast cancer and inhibits cell apoptosis [ 17 ]. Liu et al also provided strong evidence that upregulation of QPRT promotes breast cancer progression [ 16 ]. Earlier work indicated that QPRT might have an antiapoptotic function (Ullmark et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/Akt signalling pathway is activated in various cancers and has been proven to be one of the most important signalling pathways in cancer development [ 30 ]. The PI3K/Akt signalling pathway has attracted increasing attention in breast cancer research as activating this pathway can promote breast cancer cell proliferation, inhibit apoptosis [ 31 ], and modulate cell invasion [ 16 ]. Human epidermal growth factor receptor-2 (HER2) is involved in the development of breast cancer through the PI3K/Akt/mTOR pathway [ 27 ], and the PI3K/Akt/mTOR pathway is an important pathway involved in chemoresistance and survival of triple-negative breast cancer (TNBC) [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation